"Was that interesting?" & "Does it matter?": The implications of on-task learning experiences. (March 2023) - Fryer, Luke K.; Zeng, Lily M.; Shum, Alex; Ho, Charlene C.; Wong, Chi-Wing
Abstract: Interest is a critical fuel for and outcome of learning. Building on and refocusing the Four-Phase Model of interest development, this study provides a window into the ecology of the learning experience and interest it generates. This research uses a novel mobile assessment platform to test learning experiences in three university courses (Organic chemistry, biochemistry, and introduction to physics for non-majors) and pilots a micro-analytic approach to capturing these experiences during lectures/tutorials. Students' interest in tasks, a single class, and the domain of study were collected with short surveys through an online mobile platform during class, immediately following task experiences. Latent variance-based modelling suggested strong forward connections between interest in most tasks. The connections between prior knowledge and interest with a future interest in course tasks varied strongly and were dependent on the nature of the tasks. The nuance of these connections and their implications for mobile assessment are discussed. Highlights: Four micro-analytic studies in university STEM courses students' interest and prior knowledge. PLS-SEM tested longitudinal interconnects: knowledge, Domain interest, Course interest and Task interest. Interest in tasks were strongly and differently impacted by prior knowledge and Domain interest.